Molecular evolutionary relationships of Vietnamese and global pulmonary Paragonimus species in the family Paragonimidae and suborder Xiphidiata (Platyhelminthes: Trematoda) - Khue, Nguyen Thi; Linh, Pham Thi Khanh; Roan, Do Thi; Huong, Doan Thi Thanh; Doanh, Pham Ngoc; Hoa, Le Thanh (Vietnam Journal of Biotechnology, 2021)
Paragonimiasis, caused by Paragonimus species belonging to the family Paragonimidae of the suborder Xiphidiata (Platyhelminthes: Trematoda), often occurs in poor, upland, ethnic minorities, in Vietnam and the world. Asian Paragonimus species are distributed from Japan, South Korea, along with North and Southeast China, North-West and Central Vietnam, the Philippines, Thailand, Bangladesh, India, and Sri Lanka. There are various genetic variants, strains, and genotypes forming different complexes and evolutionary lineages. The 18S, 28S rDNA sequences and the intergenic transcribed spacer regions (ITS-1, ITS-2) of nuclear ribosomal transcription units are commonly used as molecular markers in genetic studies and phylogenetic analyses. We obtained a portion of 28S rDNA (domains D1–D3) of Paragonimus spp. including P. heterotremus (from Vietnam), P. ohirai (Japan), P. iloktsuenensis (Japan), and P. westermani (India and Vietnam) and conducted phylogenetic analysis for molecular evolutionary studies. The results showed that the family Paragonimidae formed the biggest cluster in a phylogenetic tree, which comprises of 46 sequences of 11 species belonging to 11 subgroups, among which the P. westermani complex of strains originating from China, Korea, Japan, India, Philippines, Malaysia, and Vietnam is present. P. westermani complex is arranged in a position of "sister" (sister group) with the subgroup P. siamensis. The P. heterotremus and P. ohirai complexes, and the P. miyazakii, P. harinasutai, P. mexicanus, P. kellicotti, and P. macrorchis complexes are clustered in a common population. P. westermani of Vietnam is in close proximity to the East Asian strains, as of which has been previously reported. P. ohirai and P. iloktsuenensis are considered “sibling” species, sharing the same clade. Phylogenetic analysis using the 28S rDNA sequences directly presented species position and their molecular evolutionary relationships in the families Paragonimidae, Troglotrematidae, Nanophyetidae, and Collyriclidae. Evolutionary analysis has also clarified a number of complex delineation problems and made a clear nomenclature for Paragonimus sp. of Vietnam, in particular, which has scientific grounds merited to recognize as that it is really the P. westermani species.